2017
DOI: 10.3892/etm.2017.4380
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS complex is a prognostic marker of microvascular reperfusion and changes in LV function occur in patients with ST elevation myocardial infarction who underwent primary percutaneous coronary intervention

Abstract: The present study aimed to investigate the in-hospital and long-term prognostic value of fragmented QRS complex (fQRS) for microvascular reperfusion and changes in left ventricular (LV) function in patients with ST elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PCI). A total of 216 patients with STEMI undergoing primary PCI were included in the current study. Patients were divided into two groups based on the presence (n=126) or absence (n=90) of fQRS followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Recent studies have shown that fQRS may be of significant prognostic value in patients with STEMI undergoing reperfusion therapy 6, 7, 8, 9, 10. STEMI patients with fQRS in electrocardiogram (ECG) tend to have higher cardiac biomarker levels, higher inflammatory markers, higher angina to balloon time, lower left ventricular function, extensive coronary artery involvement, and poorer reperfusion parameters 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that fQRS may be of significant prognostic value in patients with STEMI undergoing reperfusion therapy 6, 7, 8, 9, 10. STEMI patients with fQRS in electrocardiogram (ECG) tend to have higher cardiac biomarker levels, higher inflammatory markers, higher angina to balloon time, lower left ventricular function, extensive coronary artery involvement, and poorer reperfusion parameters 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…These forms occur as a result of non-homogeneous electrical activation of either ischemic injured ventricular myocardium or myocardial scar. [14] Many investigators had reported the significant association between the presence of fQRS and the short-term and long outcome and mortality in STEMI patients [15][16][17] However, our study was conducted on non ST-segment elevation acute coronary syndrome patients. In patients with various presentations of IHD, the presence of fQRS was associated with myocardial scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their similar clinical presentations and treatment strategies, Puelacher and his colleagues have found that all-cause mortality was significantly higher in patients with NSTEMI compared with UA patients despite of similar incidence of future non-fatal myocardial infarction was comparable between the two groups. [17] So, it seems that early detection of NSTEMI among patients with acute coronary syndrome might be useful. The standard method of differentiation between NSTEMI and UA is measuring of cardiac biomarkers and the most important and widely used in practice is the high-sensitivity cardiac troponin (hscTn) [7,8] However, there is a lag time hscTn between the beginnings of symptoms of NSTEMI to the rise of hscTn to a level that could diagnose NSTEMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies [ 29 31 ] reported that the occurrence of myocardial coronary perfusion abnormality in fQRS patients is significantly enhanced, and the predictive value for the cardiac death is significantly higher compared to non-fQRS patients. A previous study [ 32 ] reported that the fQRS complex acts as a prognostic marker for microvascular reperfusion and LV dysfunction. However, the present study investigated the function of fQRS in the adverse cardiac events in STEMI patients for the first time.…”
Section: Discussionmentioning
confidence: 99%